CALIFORNIA SHORT AND LONG-RANGE PLANS. (Tufts Archival Research Center, 2007)
Report on the state of affairs with regard to the tobacco industry in California. Identifies the short term strategy as addressing the excise tax issue in California nod the long term strategy as attempting to restructure the state's finances. Discusses the plan for accomplishing both goals which includes work in public relations, garnering support from allied organizations and increased lobbying.